PENERAPAN STRATEGI MARKETING MIX PADA PERUSAHAAN FOREX STUDI KASUS : PT INTERNATIONAL BUSINESS FUTURE - Prawiranegara, Philip; Jane, Orpha (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
Business development in Indonesia continues to increase, one of these businesses is the trading business on the foreign exchange market. The 7P marketing mix is a method to introduce the most effective forex business. PT International Business Future is a company that operates in the forex business sector. The purpose of this study is to determine the assessment and response of investors to the marketing mix at PT IBF. The research is descriptive qualitative with the research method used was a case study at PT IBF Bandung branch at Mohammad Rhamdan. The research used an interview system and distributed questionnaires. The Results show that the product and promotion variables show a very positive response from investors, which means these two variables have succeeded in becoming a good marketing mix strategy. Meanwhile, the lowest but still positive variables are in the place variable, especially the company image and in the people variable, sales professionalism in explaining the product. Variables that show a positive response can continue to be improved while the lowest variables can be made stronger changes or improvements. The results of the cross-tabulation show that respondents with higher education tend not to agree with the promotion, which means that PT IBF needs to provide a new marketing strategy.